Analysis of Causes of Mental Health Disorders in Pregnant Mothers in Developing Countries : Scoping Review - Marcelis Stia Anggraini; Asri Hidayat; Remedioz L. Fernandez (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Pregnancy is a time of increased vulnerability to the development of anxiety and depression. Mental health of pregnant women needs attention, because it will have an impact on their physical health. Anxiety and depression in pregnant women have a high risk of abortion, impaired fetal growth and even in serious conditions can be a cause of suicide. Pregnancy depression is associated with negative effects such as low birth weight, prematurity and cognitive or behavioral problems on the child. The role of health workers in maternal and child health services (MCH), so far has still encountered obstacles in knowing for sure the mental health status of pregnant women. So far, the focus of examination of pregnant women at health service centers is still limited to physical health checks, such as blood pressure monitoring, hemoglobin levels, physical complaints of pregnant women, weight gain and monitoring of nutritional intake, while mental health examinations have not become a special concern, especially in developing countries where there are still very few screenings related to mental health examinations during the perinatal period.To analyze the causes of health problems in pregnant women in developing countries. Scoping review With stages, among others: Identifying the research question, Identifying relevant studies,. Study selection, Charting the data, Collating, reporting the results, This review raises four themes that are the most common causes of mental health disorders during pregnancy in developing countries, namely economic factors, sexual partner violence, family support and education level.